Colite por citomegalovirus em paciente transplantada renal: relato de caso e revisão da literatura - Hossne, Rogério Saad [UNESP] (2007)
Cytomegalovirus infection frequently develops in immunocompromised patients, either in post-transplanted patients or in patients with diseases that affects the immune system, such as AIDS; we present a case of a 49 year old female patient in late post surgery (14 years) of a kidney transplant, using immunosuppressing medication. The patient presented abdominal pain, weight loss and initial diarrhea, she was hospitalized and developed severe hematochezia and hypotension. The patient was submitted to a colonoscopy and presented friable aspect mucosa, with aphthoid ulcers, fibrin and pseudopolyp formation; biopsy revealed cytomegalovirus. Her condition did not improve after the use of foscarnet, and surgical treatment was necessary. The patient died 5 days later.